2013
DOI: 10.1007/s00268-013-2289-x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Volume Response to Liver Graft Reperfusion Stress in Cirrhotic Patients

Abstract: Latent cardiac dysfunction among LT recipients, considered to be abnormal stroke volume response to unclamping of portal vein, is very prevalent. SVRI and LAD were independent predictors of inadequate responses. This condition deserves special attention since it may aggravate the early postoperative course of LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The model for end-stage liver disease (MELD) score was weighted for hepatocarcinoma according to Sharma and colleagues 13 (range 6-40). General anesthesia was administered as previously described, 14 blood products were transfused according to our protocol that we started from 2007. 15 Patients under coumarin drugs were preoperatively reversed with prothrombin complex concentrate (Octaplex; Octapharma, Canada) until the international normalized ratio < 2.…”
Section: Methodsmentioning
confidence: 99%
“…The model for end-stage liver disease (MELD) score was weighted for hepatocarcinoma according to Sharma and colleagues 13 (range 6-40). General anesthesia was administered as previously described, 14 blood products were transfused according to our protocol that we started from 2007. 15 Patients under coumarin drugs were preoperatively reversed with prothrombin complex concentrate (Octaplex; Octapharma, Canada) until the international normalized ratio < 2.…”
Section: Methodsmentioning
confidence: 99%
“…A subset of patients undergoing LT develop an abnormal cardiac response characterized by a decrease in stroke work despite an increase in preload[ 18 ]. This is associated with a longer post-operative intubation time and poor surgical outcomes[ 18 , 19 ].…”
Section: Hemodynamic Changes During Ltmentioning
confidence: 99%
“…A subset of patients undergoing LT develop an abnormal cardiac response characterized by a decrease in stroke work despite an increase in preload[ 18 ]. This is associated with a longer post-operative intubation time and poor surgical outcomes[ 18 , 19 ]. Although these cardiovascular complications can be anticipated, the cardiac response during LT tends to vary significantly between individuals depending on competing comorbidities and presence of preexisting cardiomyopathy[ 20 ].…”
Section: Hemodynamic Changes During Ltmentioning
confidence: 99%
“…61 A sudden increase in preload is also seen after graft reperfusion during liver transplantation. 28,62 Patients with CCM and other cardiomyopathies cannot accommodate this volume loading, resulting in increased pulmonary capillary wedge pressure (PCWP), hepatic congestion, and hemodynamic instability. 63 Escobar et al 62 showed that preoperative low-systemic vascular resistance and increased left atrium (LA) were independent predictors of inadequate cardiac response after graft reperfusion.…”
Section: Clinical Featuresmentioning
confidence: 99%